2022
DOI: 10.1089/big.2021.0043
|View full text |Cite
|
Sign up to set email alerts
|

Extended Kalman Filter-Based Power Line Interference Canceller for Electrocardiogram Signal

Abstract: Cardiac diseases constitute a major root of global mortality and they are likely to persist. Electrocardiogram (ECG) is widely opted in clinics to detect countless heart illnesses. Numerous artifacts interfere with the ECG signal, and their elimination is vital to allow medical specialists to acquire valuable statistics from the ECG. The utmost artifact that is added to the ECG signal is power line interference (PLI). Numerous filtering methods have been employed in the literature to eliminate PLI from noisy E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…S. Tahir proposed the use of an extended Kalman filter for the purpose of canceling out the noise associated with an ECG signal [24]. The evaluation was performed for four cases of power line interference (PLI).…”
Section: Literature Reviewmentioning
confidence: 99%
“…S. Tahir proposed the use of an extended Kalman filter for the purpose of canceling out the noise associated with an ECG signal [24]. The evaluation was performed for four cases of power line interference (PLI).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A 34-bit fixed-point Normalized Least Mean Square (NLMS) and a 34-bit fixed-point Improved Proportional Normalized Least Mean Square (IPNLMS) based VLSI architectures were proposed for accurate Fetal Electro-CardioGram (FECG) and Fetal Heart Rate (FHR) processing in [14]. In [15], it was shown that the extended Kalman filter-based adaptive noise canceller system outperforms the state-space recursive least squares filter-based adaptive noise canceller system and effectively eliminates PLI from ECG signals. Moreover, the performance evaluation of both single stage and multistage adaptive noise cancellers using various adaptive algorithms was compared for the removal of 60 Hz PLI and other artifacts from the ECG signal in [16].…”
Section: Introductionmentioning
confidence: 99%